Tecnologia de sementes de Vernonanthura discolor (Spreng.) H. Rob. e Byrsonima crassifolia (L.) H.B.K. - Grzybowski, Camila Ribeiro de Souza (2016)
Orientador : Profª. Drª. Maristela Panobianco Vasconcellos